Adaptacja systemu pomiarowego i metoda przygotowania danych do NIALM = Adaptation of measuring system and method for preparing data for reasearches of NIALM algorithms - Dowalla, Krzysztof; Łukaszewski, Robert; Wójcik, Augustyn; Januszewski, Marcin (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The paper presents the measurement system allowing for obtaining data necessary for evaluation of non-intrusive load monitoring algorithms. The system enables multi-channel measurement of voltage and current signals at two acquisition locations with different sampling frequencies.
Keywords: systemy pomiarowe; energia elektryczna; NIALM; monitorowanie zużycia energii elektrycznej